Sources and management of Pseudomonas syringae pv. phaseolicola and Pseudomonas syringae pv. syringae Epiphytes on dry beans in Colorado - Legard, D.E.; Schwartz, Howard F. (Scientific Societies, 1987)
Investigations during 1984 and 1985 demonstrated that Pseudomonas syringae pv. phaseolicola (Psp) and Pseudomonas syringae pv. syringae (Pss) occur as epiphytes on dry beans in Colorado. Populations of syringae-type pseudomonads (STPs) were detected on volunteer bean plants throughout northeastern Colorado. Commercial bean seedlings were free of STPs, suggesting that western-grown, certified seed lots had no, or relatively low, levels of STP contamination. Epiphyte population enumeration by replicate dilution plating was facilitated by a modification of Harris and Sommers dilution plate frequency method. Populations of STPs increased in experimental plots not sprayed with cupric hydroxide until early flowering. Bacterial populations in these plots decreased after spraying and then increased rapidly as plants matured. Pss dominated the STP epiphytic populations isolated from young plants in 1984, whereas Psp became predominant later in the season in 1984 and 1985. Cupric hydroxide foliar sprays significantly reduced or limited establishment of STPs on bean foliage. Determination of the effect of bactericides on epiphyte populations provides essential information needed to improve control strategies for halo blight and bacterial brown spot of dry beans.